Fundamental Electrochemical Insights of Vertically Aligned Carbon Nanofiber Architecture as a Catalyst Support for ORR. Issue 6 (15th April 2020) - Elangovan, Ayyappan; Xu, Jiayi; Brown, Emery; Liu, Bin; Li, Jun
Abstract : Three-dimensionally (3D) architectured carbon supports have received great attention for fuel cell catalysts. However, the complicated structure makes the assessment of catalytic properties difficult using the conventional rotating disk electrode (RDE) method. This paper reports a systematic study on oxygen reduction reaction (ORR) with ion-beam sputtered Pt catalyst (at Pt loadings of 6.5–43 μ g cm −2 ) on a vertically aligned carbon nanofiber (VACNF) array, consisting of conically stacked graphitic microstructures. The RDE studies reveal that thick 3D architecture of VACNFs exhibits enhanced limiting current density that deviates from the Levich equation for conventional thin-film catalysts. Nevertheless, useful information can be derived from RDE experiments with such systems. Molecular models representing VACNFs have been constructed to explore their capacity as catalyst supports for ORR. Platinum atoms form strong bonds at the open graphitic edges in VACNF, corroborating the role of VACNF in stabilizing Pt. Density Functional Theory (DFT) calculations further elucidate the two-electron and four-electron ORR pathways on the bare VACNF and Pt/VACNF catalysts, respectively. Furthermore, the Pt/VACNF catalysts show enhanced tolerance to methanol oxidation and a higher ability to recover from carbon monoxide poisoning in comparison to the benchmark Pt/C catalysts. These results provide critical insights for developing future high-performance electrocatalyst supports.